Activation of α1A‐adrenoceptors desensitizes the rat aorta response to phenylephrine through a neuronal NOS pathway, a mechanism lost with ageing. (10th May 2017) - Arce, Cristina; Vicente, Diana; Segura, Vanessa; Flacco, Nicla; Montó, Fermi; Almenar, Luis; Agüero, Jaime; Rueda, Joaquín; Jiménez‐Altayó, Francesc; Vila, Elisabet; Noguera, Maria Antonia; D'Ocon, Pilar; et al.
Abstract : Background and Purpose: A NO‐mediated desensitization of vasoconstrictor responses evoked by stimulation of α1 ‐adrenoceptors has been reported in different vessels. We investigated the involvement of each α1 ‐adrenoceptor subtype and constitutive NOS isoforms and the influence of ageing and hypertension on this process. Experimental Approach: Wistar and spontaneously hypertensive rats (SHR), 16, 32, 52 and 72 weeks‐old, were used to evaluate the desensitization process. Expression of α1 ‐adrenoceptor subtypes, endothelial NOS (eNOS) and neuronal NOS (nNOS) were determined in rat aorta and left ventricle (LV). Expression levels were also evaluated in LV of a group of heart failure patients with a wide age range. Key Results: Repeated application of phenylephrine decreased subsequent α1 ‐adrenoceptor‐mediated vasoconstriction by increasing nNOS protein expression in aorta, but not in tail or mesenteric resistance arteries, where mRNA levels of nNOS were undetectable. This desensitization process disappeared in the absence of endothelium or in the presence of L‐NAME (100 μM), nNOS inhibitors, SMTC (1 μM) and TRIM (100 μM), and 5‐methylurapidil (100 nM, α1A ‐antagonist), but not BMY7378 (10 nM, α1D ‐antagonist). The α1A /nNOS‐mediated desensitization was absent in aged SHR and Wistar animals, where the expression of α1A ‐adrenoceptors was reduced in aorta and LV. In human LV, a negative correlation was found between age and α1A ‐adrenoceptor expression. Conclusions and Implications: The α1A ‐adrenoceptor subtype, through endothelial nNOS‐derived NO, may act as a physiological 'brake' against the detrimental effects of excessive α1 ‐adrenoceptor‐mediated vasoconstriction. Reduced α1A ‐adrenoceptor‐ and nNOS‐mediated desensitization in aged patients could be involved in the age‐dependent elevation of adrenergic activity.